The Influence of PMB Content and Engagement on Instagram on the Interest of New Students at Jenderal Achmad Yani University - Tambunan, Very Verdyanto; Anggoro, Sigit; Santikarama, Irma (Jurnal Indonesia Sosial Sains, 2025)
New student admissions marketing content delivered through social media platforms like Instagram has become a crucial strategy for attracting prospective students. Jenderal Achmad Yani University utilizes Instagram as a promotional tool by displaying various information related to study programs, registration schedules, campus facilities, and student activities in engaging and engaging visual content. In addition to content quality, user engagement, such as the number of likes, comments, and other interactions, is also a key indicator in measuring the effectiveness of the promotion. This study used a quantitative approach through a survey of prospective students and followers of the official Universitas Achmad Yani Instagram account. Data analysis was conducted using multiple linear regression to determine the influence of new student admissions content and engagement on university admission intentions. The results showed that both content and engagement on Instagram significantly influenced prospective students' interest in applying to Jenderal Achmad Yani University. These findings underscore the crucial role of social media in shaping the image and attractiveness of higher education institutions. A consistent and interactive digital promotional strategy can help universities reach their target audience more effectively and increase new student enrollment intentions.